Scar management - Labadie, Jessica G.; Alam, Murad; Dover, Jeffrey S. (Procedures in cosmetic dermatology, 2026)
The book provides current, practical guidance on medical treatments, light/laser treatment, surgical and non-surgical procedures, and more, edited by the foremost pioneers in the field. Succinctly written and lavishly illustrated, this resource focuses on procedural how to's and offers step-by-step guidance on proper techniques, pitfalls, and tricks of the trade. Reviews connective tissue biology, wound healing, and scar formation. Covers the hottest topics and treatments in scar management and pigment modification today including medical, surgical, and radiation approaches, as well as the evolving landscape of lasers and other energy-based devices. Discusses common pitfalls and emphasizes how to optimize outcomes. Shares tips and tricks of the trade from practically minded, technically skilled, hands-on clinicians. Includes new chapters on minimally invasive procedures in scar management; management of keloids and hypertrophic scars; management of acne scarring; management of traumatic and burn scars; patient case studies and treatment algorithms; and more, as well as two new videos on lasers and energy-based devices. Features a wealth of color illustrations and photographs that depict cases as they present in practice, treatment algorithms, and further reading lists. An eBook version is included with purchase.